2001
DOI: 10.2176/nmc.41.100
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Histological Changes Occurring in Hydroxyapatite Cranial Reconstruction. Case Report.

Abstract: Histological changes were observed in a hydroxyapatite plate and hydroxyapatite granules used to repair a craniotomy defect and removed after 2 years and 9 months of use. The hydroxyapatite plates and granules had completely fused to the cranium, with new bone formation on the dural side extending in a three-dimensional matrix along the pores with the Haversian system in the center. New bone formation was less extensive under the artificial dura than under the normal dura. This finding suggests that the dura h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Okii et al [13] reported on histological changes observed in HA plates and HA granules, which were removed from a patient after nearly 3 years in vivo. The HA plate had fused tightly to the cranium and could be excised only by using a diamond drill.…”
Section: Discussionmentioning
confidence: 99%
“…Okii et al [13] reported on histological changes observed in HA plates and HA granules, which were removed from a patient after nearly 3 years in vivo. The HA plate had fused tightly to the cranium and could be excised only by using a diamond drill.…”
Section: Discussionmentioning
confidence: 99%
“…11 The minimum pore diameter required for bone ingrowth and angiogenesis into a scaffold is generally considered to be 100 mm. 6,12 Bioactive glasses are amorphous silica based materials that are biocompatible, bioactive, osteoconductive and even osteoproductive. 10 Their bone bonding ability has been attributed to the formation of a hydroxycarbonate apatite (HCA) layer in the surface of the glass on contact with body fluid.…”
Section: Bioactive Ceramic Scaffolds Bioactive Ceramicsmentioning
confidence: 99%
“…It is important to note that in order to repair large defects, 3‐D scaffolds are required to provide a template and support tissue growth rather than the usual powder or granular form in which bioactive glasses currently are commercially produced. Ideally the template must consist of (1) an interconnected network with large pores (greater than 100 μm) to enable tissue ingrowth and nutrient delivery to the center of the regenerated tissue;11 and (2) pores in the microporous (<2 nm) or mesoporous (2 nm < pore size < 50 nm) range to promote cell adhesion, adsorption of biologic metabolites,12 and resorbability at controlled rates to match that of tissue repair.…”
Section: Introductionmentioning
confidence: 99%